Valores de la identidad cultural en la escuela - Chinguercela Caillagua, Jimmy Rodrigo (2023)
The importance of this project focuses on the weakness of the practice of values against cultural identity, within the work or rest areas, since, in the schools, there is a variety of students from different cultures, therefore they have their clothing, languages, customs, and traditions. The objective of this research is to identify the incidence in the practice of values on cultural identity in the students of the Eighth year of Basic Education of the parallel "B" of the Educational Unit "Primero de Abril" academic period 2022-2023. The methodology is qualitative, it allows one to understand the reality of the educational context from its environment, in addition, it works with the qualities of the students, the method we used is inductive since it collects information on the aspects that are involved, the research design is from the field because the information was extracted directly from the individuals or objects of study, the techniques that were used are observation and interview with their respective instruments, observation guide, and question guide thus collecting relevant information. We concluded that maintaining the school's cultural identity is essential to fostering an environment that is stimulating for students' academic and personal growth. In summary, we developed a guide of playful activities to strengthen the cultural identity. The activities promote meaningful learning, mutual respect, and appreciation of cultural diversity, allowing students to connect with their identity and develop essential social skills for harmonious intercultural coexistence.